An echo of the Indian mutiny: the proposed banishment of Bahadur Shah II to the Cape Colony, 1857 (Historia, 2021)
-
Keywords: Indian mutiny; Behadur Shah II; Mutiny of 1857; Cape Colony; King of Delhi